Metaphor and Irony comprehension in typically developing school children: a pilot study - Ferreira, Claúdia; Alegria, Rita; Rocha, Joana Antonieta (Revista de Investigación en Logopedia, 2021)
This study aimed to analyse irony and metaphor comprehension of Portuguese school age children and analyse some of their individual differences, investigating if such factors may play a role in the comprehension of these two language elements. Two European-portuguese versions of stories from the instrument ‘Stories from Everyday Life’ were used to assess irony and metaphor comprehension in a sample of 30 children with 8 years in a Portuguese private educational institution. Individual differences (e.g., gender, number of siblings, parents’ educational levels and family history of speech and/or language disorders) were also considered. Children were able to understand metaphors and irony, as previously observed in other studies (e.g. Dews & Winner, 1997; Özçalışkan, 2007; Özçalişkan, 2005; Özçalışkan, 2007; Stites & Özçalişkan, 2013 Pexman & Glenwright, 2007). Results regarding individual differences on children’s performances showed that: i) male children performed better in both stories; ii) two children who presented a family history of speech and/or language disorders obtained lower scores than their peers; iii) two children whose parents had lower educational level than other families of participants performed worse than their peers; and iv) children who had more siblings performed better in both stories. Children’s performances on both stories were positively correlated. No signiﬁcant gender differences were found regarding irony and metaphor comprehension, however, a slight advantage was found in male children. The number of siblings was positively associated with metaphor and irony comprehension. More research is needed to clarify the influence of developmental and social variables in metaphor and irony comprehension.